In-Orbit Data Driven Identification of Satellite Inertia Matrix. Issue 15 (2018) - Nainer, C.; Garnier, H.; Gilson, M.; Pittet, C.
Abstract: This paper proposes a procedure for estimating the inertia matrix of a satellite from flight telemetry data. The Euler's equations, that govern the rotational dynamics of a satellite are considered for the modeling. The satellite system is operating in closed loop, making the estimation of the parameters more challenging from the theoretical point of view. The estimation method consists in the implementation of a closed-loop instrumental variable method, that has the capability of yielding consistent results with mild requirements on the noise properties. The performance of the proposed method is tested by Monte Carlo simulations based on a satellite model. These results are analyzed and compared to two other estimation methods.